Is urban spatial development on the right track? Comparing strategies and trends in the European Union - Cortinovis, Chiara; Haase, Dagmar; Zanon, Bruno; Geneletti, Davide (Landscape and urban planning, 2019)
•The spatial development of 175 EU cities is compared with six EU strategies.•Urban expansion (land take) halted in only two cities.•Compactness and land use mix increased in most cities.•Urban regeneration interventions were more frequent in Northern and Western cities.•The highest increase in green space occurred in Southern cities. Urban spatial development is a crucial issue for spatial planning and urban governance, ultimately determining cities’ sustainability. While a set of spatial strategies to address urban development are progressively gaining international consensus, their actual applicability is still contested. An interesting test-bed is represented by the European Union (EU), where common spatial strategies have been discussed since 1993. This paper aims to identify the main spatial strategies promoted at the EU-level and to investigate whether the recent spatial development trends of EU cities have been following the directions suggested by the strategies. By analysing 30 policy documents, we identified six main strategies: compact city, urban regeneration, functional mix, no land take, green city, and high density. For each strategy, we selected a set of indicators and applied them to the analysis of 175 cities representative of the variety of conditions across the EU. Most cities progressed towards compact city and functional mix, but almost none halted land take. Urban regeneration was more intense in Northern and Western cities, while Southern cities show the most significant increase in green spaces. Growing cities achieved a higher density, but expanded inefficiently producing abandonment of urbanized areas and fragmentation of agricultural land. Shrinking cities continued in the paradox of contemporary population loss and expansion already observed by previous studies. The results highlight potential conflicts and trade-offs in the implementation of the strategies. Similar analyses can stimulate comparison, exchange, and cooperation among cities, thus supporting the mainstreaming of non-prescriptive strategies formulated at the international level.